Video Image Compression Using Absolute Moment Block Truncation Method with Orthogonal Search Motion Estimation Technique - Kanger, Ebtesam; Muhsin, Israa; Abbas, Ban (Iraqi Journal of Science, 2023)
Image compression has become one of the most important applications of the image processing field because of the rapid growth in computer power. The corresponding growth in the multimedia market, and the advent of the World Wide Web, which makes the internet easily accessible for everyone. Since the early 1980, digital image sequence processing has been an attractive research area because an image sequence, as acollection of images, may provide much compression than a single image frame. The increased computational complexity and memory space required for image sequence processing, has in fact, becoming more attainable. this research absolute Moment Block Truncation compression technique which is depend on adopting the good points of other techniques. As well as algorithm of efficient block's position has been adopted to achieve this research. Also in this paper was introduce A modify of the orthogonal search algorithm (OSA) for searching scheme has been introduced which is contributed in decreasing the motion searching time of the successive inter frames.